Examining the Feasibility of Livestock Insurance in Mongolia - Skees, Jerry R.; Enkh-Amgalan, Ayurzana (World Bank, Washington, DC, 2014)
Herders in Mongolia have suffered tremendous losses in recent dzud (winter disasters), with livestock mortality rates of over 50 percent in some locales. This study examines the feasibility of offering insurance to compensate for animal deaths. Such an undertaking is challenging in any country. Mongolia offers even more challenges given the vast territory in which herders tend over 30 million animals. Traditional approaches that insure individual animals are simply not workable. The opportunities for fraud and abuse are significant. Monitoring costs required to mitigate this behavior would be very high. This study focuses on the potential for using the livestock mortality rate at a local level (for example, the sum or rural district) as the basis for indemnifying herders. Applications of index insurance are growing around the world, although no country has so far implemented such insurance for livestock deaths. But few countries have such frequent and high rates of localized animal deaths as does Mongolia, and it is one of the few countries that perform an animal census every year. This concept may therefore be precisely what is needed to start a social livestock insurance program. Just as important, the insurance that is used in Mongolia should not interfere with the exceptional efforts that experienced herders take to save animals during severe weather. Using an individual insurance may, in fact, diminish these efforts. Herders may ask, "Why should I work so hard to save my animals if I will simply be compensated for those that are lost?" Since the index insurance would pay all herders in the same region the same rate, the incentives for management to mitigate livestock losses remain strong. No one would reduce their effort to collect on insurance. Those who increase their efforts during a major event (dzud) would likely be compensated for this effort even though they do not lose livestock. In some cases, they could reasonably expect to receive payments that would compensate for the added effort or the added cost of trying to save their livestock.